Aspiration thrombectomy and intracoronary tirofiban via GuideLiner® catheter for a thrombosed aneurysmal vessel. (March 2017) - Fry, James; Naqvi, Ali; Bahia, Amit; Seto, Arnold
A 52-year-old Asian male with no traditional risk factors for coronary artery disease presented with acute coronary syndrome. Coronary angiography showed complete thrombotic occlusion of the left circumflex with a large thrombus burden in the setting of diffuse aneurysmal enlargement of the coronary arteries consistent with antecedent Kawasaki disease. Manual thrombectomy with adjunctive intracoronary tirofiban was performed utilizing the GuideLiner catheter ® (Vascular Solutions, Inc., MN, USA). Stent implantation was deferred. Follow-up imaging 48 h later showed preserved coronary flow and decreased thrombus burden. The GuideLiner catheter, a monorail guiding device, served a novel role in thrombus aspiration and intracoronary medication delivery.